Ageing of PBF‐Grade Poly(Phenylene Sulfide) Powder and its Effect on Critical Printability Properties. Issue 3 (1st February 2021) - Chatham, Camden A.; Das, Arit; Long, Timothy E.; Bortner, Michael J.; Williams, Christopher B.
Abstract: Poly(phenylene sulfide) (PPS) is a high‐performance polymer suiting the needs of powder bed fusion (PBF) early‐adopter industries. Although there are many benefits to PBF's powder bed‐based, one drawback is thermal ageing of the powder not incorporated into printed parts. Ideally, unfused powder can be reused in future builds; however, it is unlikely that critical printability properties of the thermally aged powder will remain unchanged. Changes in properties lead to either limited reuse through a practice of mixing used and new powder, or elimination of all powder after each build. In this paper, the authors report effects of thermal ageing in simulated printing conditions on properties of PPS critical to PBF processing. PBF‐grade PPS powder is exposed to process‐mimicking conditions. Properties relevant to the three PBF manufacturing process sub‐functions are assessed for the aged powders. Single‐layer prints are made using aged powder to observe polymer‐PBF interactions ad machina. Significant and systematic deviations from the as‐received state of the powder are observed for thermal and coalescence related properties with increasing exposure time and temperature. These changes are interpreted both in terms of physical and chemical changes in PPS and in terms of how these changes may impact the PBF printing process. Abstract : This manuscript details the effects of thermal exposure on powder, thermal, flow, and mechanical properties of a "PBF‐grade" poly(phenylene sulfide) powder. The thermal exposure process is designed to mimic extensive reuse in the context of powder bed fusion additive manufacturing and the chosen polymer properties have been previously shown to be critical to PBF manufacturing success.